OPTIMALISASI PRODUKSI DENGAN MENGINTEGRASI ACTIVITY- BASED COSTING DAN THEORY OF CONSTAINTS (Fokus Ekonomi, 2003)
Every firm faces limited resources and limited demand of each product. These ilimitations are called constraints. Theory of constraints (TOC) recognizes that performance any organization is limited by its constraints. TOC then developes a spesific approach to manage constraints to support the objective of conntinues improvement. while ABC measure the usage of resource the usage of resource with respect to the demand place on production activity. if demand on an activity is below the level of servicess supplied. ABC assign the cost of the excess resources to the unused capacity. Under ABC the cost of unused capacity is used for resource allocation decisions to the better match the supply and demand for an activity's resources. thus ABC and TOC have similar objectives but the means used to achieve these objectives differ significantly. this article discuses how aspect of the TOC may be integrated with ABC as proposed by Kee (1995) integrating ABC with principles from the TOC provide an expanded framework foe understanding the economic consequences of production-related decisions.Keywords: Activity Based Costing, theory of constraints, production related decisions.